Novel polymer-inorganic solid-state reaction for the synthesis of CdS nanocrystallites - Kanade, K. G.; Hawaldar, Ranjit R.; Pasricha, R.; Radhakrishnan, S.; Seth, T.; Mulik, Uttam P.; Kale, B. B.; Amalnerkar, Dinesh P. (Materials Letters, 2005)
We offer a novel polymer-inorganic solid-state reaction route for the in situ generation of nanochalcogenide semiconductor in the network of polymer which itself acts as a chalcogen source. We have exemplified feasibility of this route by reacting CdI2 with engineering thermoplastic polyphenylene sulphide (PPS). These two reactants in 1:1 and 10:1 molar ratios were simply heated at the crystalline melting temperature of PPS. The resultant products were characterized by X-ray diffractometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM, with selected area electron diffraction). The prima facie observations revealed the formation of cubic nanocrystallites of US with the particle size ranging from 6 to 20 nm entrapped in modified (cyclized) PPS matrix when the reactants were taken in 10:1 molar ratio. A tentative mechanism has been suggested for such hitherto unattempted solid-state reaction. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdS nanocrystallites; Semiconductor; solid-state reaction; Thermoplastic polymer matrix

Rapid phase-controlled microwave synthesis of nanostructured hierarchical tetragonal and cubic beta-In2S3 dandelion flowers - Naik, S. D.; Jagadale, Tushar C.; Apte, S. K.; Sonawane, S.; Kulkarni, M. V.; Patil, S. I.; Ogale, Satishchandra B.; Kale, B. B. (Chemical Physics Letters, 2008)
Phase controlled synthesis of hierarchical nanostructured beta-In2S3 dandelion flowers is realized by a rapid microwave solvothermal process using indium metal, nitric acid and thiourea as precursors. The tetragonal and cubic phases of the compound have been successfully and separately stabilized in the same type of dandelion morphology by using aqueous-mediated and methanol-mediated synthesis, respectively. The possible mechanism responsible for phase control is discussed. Optical properties of the flowers as well as their hydrogen generation capability by photodecomposition of H2S under visible light are also reported. (c) 2007 Elsevier B.V. All rights reserved.

Nanocrystalline Mn-Zn-ferrite by novel oxalato-hydrazinated complex method - Kanade, K. G.; Amalnerkar, Dinesh P.; Potdar, H. S.; Kale, B. B. (Materials Chemistry and Physics, 2009)
We report here for the first time the synthesis of technologically important ferrite, using a metal oxalato-hydrazinate (MOH) complex method. The MOH complex of iron-manganese-zinc was synthesized at room temperature using the precursors, ferrous ammonium sulphate, manganese acetate and zinc acetate. Thermo-gravimetric studies of MOH intermediate showed complete phase formation of MnZnFe(2)O(4) at 280 degrees C. XRD data showed the formation of single phase cubic spinel MnZnFe(2)O(4). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) demonstrate the spherical shape particle morphology. TEM images indicated the particle size of ferrite powder in the range of 20-36 nm. Magnetization of synthesized nano-sized Mn(0.69)Zn(.0.19)Fe(2.12)O(4) was observed coercive force (H(c)) at 127.82 Oe with a saturation magnetization (M(s)), 34.5 emu g(-1) using vibrating sample magnetometer (VSM) at room temperature. Mossbauer study of nano-sized ferrite powder showed super-paramagnteic behavior. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic materials; Mn-Zn-ferrite; Nanostructures; Optical properties

Polymer-embedded stannic oxide nanoparticles as humidity sensors - Hatamie, Shadie; Dhas, Vivek V.; Kale, B. B.; Mulla, Imtiaz S.; Kale, Sangeeta N. (Materials Science & Engineering C-Biomimetic and Supramolecular Systems, 2009)
Stannic oxide (SnO(2)) nanoparticles have been suspended in polyvinyl alcohol (PVA) matrix in different PVA: SnO(2) molar ratios ranging from 1:1 to 1:5 using simple chemical route. This suspension was deposited on ceramic substrate and upon drying was carefully detached from the substrate. SnO(2)-embedded self-standing, transparent and flexible thin films were hence synthesized. Transmission electron microscopy (TEM) and Xray diffraction (XRD) techniques show the rutile tetragonal structure of SnO(2) with particle size similar to 5 nm. UV-Visible spectroscopy demonstrates the band gap of 3.9 eV, which does not alter when embedded in polymer. Fourier transform infrared spectroscopy (FTIR) reveals that the properties of SnO(2) do not modify due to incorporation in the PVA matrix. The structures work as excellent humidity sensors at room temperature. For a critical PVA:SnO(2) molar ratio of 1:3, the resistance changes to five times of magnitude in 92% humidity within fraction of second when compared with resistance at 11% humidity. The sample regains its original resistance almost instantaneously after being removed from humid chamber. Nanodimensions of SnO(2) particles and percolation mechanism related to transport through polymer matrix and water molecule as a carrier has been used to understand the mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: humidity sensor; Nanoparticles; Polymer; Stannic oxide

Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures